Território e memória: a construção da territorialidade étnica da Comunidade Quilombola Grilo, Paraíba - Maracajá, Maria Salomé Lopes (2014)
In addressing the ethnic-racial issue, we do so with reference to some issues of political, ideological, social and identity. Therefore, this dissertation aimed to analyze the process of construction of the territory and the ethnic territoriality in the maroon community Grilo, based on memorialistic reports and founding myths. The investigated community is located in the municipality of Riachão do Bacamarte, in the Mesoregion of Agreste Paraibano. In this investigation we are going to emphasize the relations and the resistance process of black men and black women from Grilo in the construction of the material and immaterial identity in their territory. From the theoretical and methodological standpoint we emphasize the importance of interdisciplinary debate in geography, in this context, and seeking to extend our gaze in this investigation, we have been reviewing the literature on the topic in documents and bibliographies, as well as field work which constitutes the most important step in the elucidation of the social, political and cultural phenomena in the community. Based on the above, we highlight that the combination of these methodologies enabled the construction of the text that makes up this dissertation. Thus, some issues have led us to affirm that the territory of the maroon community Grilo represents to the group not only ownership of a territory marked by power relations as a political strategy, but the maintenance of the memory inherited from ancestors and passed on to descendants which materialize in dances, neighborly relations, customary solidarity, among other aspects that contribute to the construction of territoriality